Distinctive presentation of neurobrucellosis as myelitis: A case report and literature review - Jiali Yin; Wei Gu; Ying Huang; Zhengnan Li (Indian Journal of Pathology and Microbiology)
Brucellosis is a zoonotic infectious allergic disease caused by Brucella that is widely distributed throughout the world. Brucella can invade various systems of the human body, such as the joints, the reproductive system, the spine, and the nervous system. Among patients with brucellosis, neurobrucellosis (NB) mainly manifests as nervous system symptoms in only 1.7–10% of patients and can cause a misdiagnosis. We reported a case of NB that presented as myelitis as the main clinical presentation and reviewed the relevant literature. It is suggested that clinicians should consider NB, especially atypical neurological symptoms, when there is a suspicious contact history.